Adjacent location of the bac gene and two-component regulatory system genes within the putative Streptococcus agalactiae pathogenicity island - Dmitriev, A; Yang, Y H; Shen, A D; Totolian, A (Folia microbiologica, 2006)
A chromosomal DNA fragment of 8992 bp in size that has not been previously identified in Streptococcus agalactiae, was cloned and sequenced from strain 98-D60C. In particular, this 8992-bp fragment contained genes homologous to the sensor histidine kinase gene and the DNA-binding response-regulator gene of Streptococcus pneumoniae, and S. agalactiae bac gene. Structural and genetic features of the 8992-bp fragment were highly similar to those specific for bacterial pathogenicity islands. Analysis of epidemiologically unrelated S. agalactiae strains revealed that this fragment was present only in bac gene-positive strains. The possible origin of the 8992-bp fragment in S. agalactiae and its significance for molecular mechanisms of "bacteria-host" interactions are discussed.
Keywords: Molecular Sequence Data; Sequence Homology, Nucleic Acid; Virulence Factors; DNA, Bacterial; těhotenství; Gene Expression Regulation, Bacterial; Streptococcus agalactiae; antigeny bakteriální; DNA bakterií; Antigens, Bacterial; Bacterial Proteins; Streptococcus pneumoniae; ženské pohlaví; genomové ostrovy; Humans; Pregnancy; Genomic Islands; regulace genové exprese u bakterií; sekvenční homologie nukleových kyselin; molekulární sekvence - údaje; faktory virulence; Female; bakteriální proteiny; lidé